Physical Properties and in Vitro Simulated Gastrointestinal Digestion Characteristics of Polygonatum cyrtonema Hua Powder with Different Particle Sizes - Chenchen ZHAO; Jiahui LÜ; Chang LIU; Ruonan TONG; Mengjin WANG; Heng LIU; Lihua XING; Jiao YU; Luna GENG; Nianjun YU (Shipin gongye ke-ji)
To investigate the functional effects of superfine grinding treatment on Polygonatum cyrtonema Hua powder, in this study, the sample was ground and sieved by pharmacopoeia test sieves (50, 100, 200 and 325 mesh) to prepare P. cyrtonema Hua powder with different particle sizes. Its physical properties were studied using scanning electron microscopy and Fourier transform infrared spectroscopy, while the in vitro gastrointestinal digestion process was simulated. The results showed that the particle size of P. cyrtonema Hua powder exhibited a significant difference (P<0.05) following grinding and sieving treatment. The grinding process only destroyed the surface structure of the powder, but did not destroy the molecular structure of the powder. The angle of repose and solubility of P. cyrtonema Hua powder exhibited a continuous increase with decreasing particle size, while bulk density, wettability and water holding capacity showed a decreasing trend. Additionally, the polysaccharide content of the sample with 200 mesh (15.37%) was significantly higher than that of other samples (P<0.05). Moreover, the polysaccharide release content of the powder with 200 mesh (75 μm, ultrafine powder Ⅰ) during in vitro gastrointestinal digestion was higher than that of other powders. Ultrafine powderⅠalso had a certain antioxidant ability. In summary, when the powder of P. cyrtonema Hua is sieved by 200 mesh sieve, the content of polysaccharide released is the highest. This experiment provides a theoretical basis for the practical application of P. cyrtonema Hua powders.